Time‐Varying Asset Volatility and the Credit Spread Puzzle - DU, DU; ELKAMHI, REDOUANE; ERICSSON, JAN (Journal of Finance, 2019)
ABSTRACT Most extant structural credit risk models underestimate credit spreads—a shortcoming known as the credit spread puzzle. We consider a model with priced stochastic asset risk that is able to fit medium‐ to long‐term spreads. The model, augmented by jumps to help explain short‐term spreads, is estimated on firm‐level data and identifies significant asset variance risk premia. An important feature of the model is the significant time variation in risk premia induced by the uncertainty about asset risk. Various extensions are considered, among them optimal leverage and endogenous default.